VISUAL AVATAR IDENTIFICATION ON ONLINE GAME PLAYERS - Mustikasari, Bunga Fefiana; Kusuma Wardani, Nuril; Yulia Nisa, Rachma (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2024)
There are many game system features in an online game and one of them is the avatar system. Avatar here is a system in the game, that gives player on the game an opportunity to dress up visual of their character according to what they want. Avatar has various types and forms that can be choose. This research aims to learn what kind of visual design avatar is preferred by online game players, which will provide an overview for game designers to create avatars in the game. This study uses a virtual ethnographic method that is connected with dramaturgical theory, how a person plays a role in the world of online games by using this avatar system. The results showed that avatars with style that match in real life are still more in demand than avatars with shapes that tend to be unique. Even though sometimes game players play different roles in the game world, they still tend to dress up their characters with visuals that match their style in real life in terms of avatar.